Web-based Ukp Public Health Center Services System Using the Waterfall Method - Fatmariani, Fatmariani; Saputra, Andri; Sari, Lindia Guspita (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Basic health services for the community are community health centers which have Health Service Units (UKP). UKP provides general health services to the community, which has many polyclinics and is interconnected with doctors, patients and administration. So far, in processing service data, there have been difficulties in general polyclinic units when receiving patient information, which is still done by recording it in a book, so there are often errors in information in patient registration services that should be received by the polyclinic that corresponds to the target polyclinic. The storage of patient data based on poly is not yet organized because the files that are stored and archived do not exist in each unit, so that when presenting data and searching you have to confirm who is archiving it, making it difficult for the data or information service department and services to be hampered. The method used in this research is the Waterfall method. This service system uses the waterfall method. The service system provides benefits in inputting and presenting data, searching for patient data such as registering online, then checking medical records to go to the clinic, online medical record results and viewing prescription information, then doctors can meet patients who carry out examinations. This system can provide good benefits and increase effectiveness and efficiency in health services for the surrounding community.